'For As Yet They Did Not Know the Scripture' (John 20:9): A Study in Narrative Time. (May 2014) - Moloney, SDB, AM, FAHA, Francis J.
Reference to 'the Scripture' that Peter and the Beloved Disciple do not 'yet' understand in John 20:9 remains a problem for interpreters of John. Which passage from Israel's Sacred Scriptures lies behind this conclusion to the episode of the two disciples at the empty tomb? This essay argues that John 20:9 is part of a larger narrative and theological strategy (see also 2:22; 12:16; 20:30–31) that presents the Gospel of John as 'Scripture.' The disciples, players in the story, do 'not yet' know this Scripture. A later generation, those who have the Gospel of John in hand, who have not seen yet believe (v. 29), have access to a Scripture 'written' that they may go on believing (vv. 30–31).